Synthesis, characterization, and biological applications of semiconducting polythiophene‐based nanoparticles. Issue 1 (20th November 2020) - Zangoli, Mattia; Di Maria, Francesca
Abstract: In recent years, polythiophene‐based nanoparticles (PT‐NPs) have attracted increasing attention because of their outstanding characteristics deriving from a wealth of properties such as charge conduction in the oxidized/reduced states, light absorption/emission at an appropriate wavelength, geometrical adaptability, thermal and chemical stability, and solubility in common solvents. Furthermore, the great synthetic flexibility of the thiophene core has allowed the engineering of a multitude of nanomaterials with made‐to‐order properties. This review is focused on the synthesis and characterization of aqueous PT‐NPs and their biological applications. In particular, both in vitro and in vivo bioapplications will be presented, in which thiophene‐based nanomaterials act as photoactuators, that is, as exogenous components capable of transforming a primary stimulus of light into a highly spatiotemporally resolved secondary stimulus able to alter cell's physiological functions. Furthermore, examples of applications of PT‐NPs in biomedicine, such as photodynamic therapy and photothermal therapy, will be discussed. Abstract : The authors present the synthesis and characterization of aqueous polythiophene‐based nanoparticles and their biological applications. In particular, in vitro and in vivo bioapplications in which thiophene‐based nanomaterials act as photoactuators will be shown.